2012
DOI: 10.1292/jvms.11-0271
|View full text |Cite
|
Sign up to set email alerts
|

The 2010 Foot-and-Mouth Disease Epidemic in Japan

Abstract: ABSTRACT. Foot-and-mouth disease (FMD) occurred recently for the first time in a decade in Japan. The index case was detected on a beef-breeding farm in Miyazaki Prefecture, Southern Japan, on April 20, 2010. After confirmation of this first case, control measures such as stamping out, movement restriction and disinfection were implemented. However, these strategies proved insufficient to prevent the spread of FMD and emergency vaccination was adopted. Up until the last outbreak on July 4, 2010, a total of 292… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
139
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 133 publications
(142 citation statements)
references
References 9 publications
2
139
0
1
Order By: Relevance
“…Our preliminary serological examination showed that the r 1 value between the O Manisa strain and the O/JPN/2010 strain isolated in the 2010 epidemic in Japan was greater than 0.3 (unpublished data). In fact, the number of FMD cases was gradually reduced in the epidemic, after emergency vaccination was practiced as one of the control measures [7].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our preliminary serological examination showed that the r 1 value between the O Manisa strain and the O/JPN/2010 strain isolated in the 2010 epidemic in Japan was greater than 0.3 (unpublished data). In fact, the number of FMD cases was gradually reduced in the epidemic, after emergency vaccination was practiced as one of the control measures [7].…”
Section: Discussionmentioning
confidence: 99%
“…In 2010, FMD occurred in Japan for the first time since 2000 [5,7]. Emergency vaccination was carried out as one of the control measures, and approximately eighty thousand vaccinated animals were destroyed.…”
mentioning
confidence: 99%
“…Dramatic photos of cattle burning in open pyres during the 2001 FMD outbreak the United Kingdom resulted in widespread public opposition to open burning. In Japan, the lack of acceptable burial sites resulted in delays in disease eradication efforts and required the Japanese government to implement a vaccinate-to-kill strategy [10]. South Korea's disease eradication efforts resulted in the destruction of 20% of the country's livestock and the creation of 4700 burial sites [11].…”
Section: Introductionmentioning
confidence: 99%
“…Although fatal cases usually occur in young animals, the high transmissibility and morbidity observed in adult animals infected by the FMD virus (FMDV) result in major economic losses to the livestock industry during disease outbreaks (1). The potentially devastating economic, social, and environmental consequences of the disease have been demonstrated dramatically during the last 2 decades by a number of different outbreaks of the disease reported around the world (2)(3)(4).…”
mentioning
confidence: 99%